Bakteri Simbion Akar Mangrove Avicennia Sp. Sebagai Pendegradasi Pewarna Tekstil - Nor Sa'adah (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2020)
Textile dye is a material that has a negative effect on environmental quality, one of the textile dyes is violet crystal. Biodegradation is one of the methods that used in waste treatment and can take advantage of microbial activity to degrade waste. Mangroves are ecosystems that are found along coastal waters in tropical and subtropical areas. Microorganisms such as bacteria are able to live and develop in mangrove roots. This study aims to isolate and identify the bacteria that live on mangrove roots morphologically and are able get degrade textile dyes. This research was conducted using experimental laboratory methods. Samples were isolated from mangrove roots obtained in Wonorejo Surabaya sterilely. The process of isolation and verification of bacterial morphology was carried out at the Microbiology Laboratory of Hang Tuah University, Surabaya. The method of isolation was carried out using the spread method, and the purification of the bacteria was carried out using the streak method. The results obtained 10 bacterial isolates from the results of isolation and morphological examination, while 2 isolates were able to degrade the violet crystal textile dye, called AB.1.2 and AB.1.5 which were indicated by the presence of clear zones.